Does Full Insurance Increase the Demand for Health Care? - Stefan Boes; Michael Gerfin (Institute for the Study of Labor (IZA), 2013)
We estimate the causal effect of having full health insurance on health care expenditures. We take advantage of a unique quasi-experimental setup in which deductibles and co-payments were zero in a managed care plan, and non-zero in regular insurance, until a policy change forced all individuals with an active plan to cover a minimum amount of their expenses. Using panel data and a non-linear difference-in-differences strategy, we find a demand elasticity of about -0.14 comparing full insurance with the cost-sharing model, and a significant upward shift in the likelihood to generate costs.
Keywords: I11; C14; 330; deductibles; health cost; quasi experiment; changes-in-changes